Descriptive dermoscopy terminology in Portuguese language in Brazil: a reproducibility analysis of the 3rd consensus of the International Dermoscopy Society - Barcaui,Carlos Baptista (2018)
Abstract: Background: Dermoscopy is a noninvasive complementary diagnostic method largely used in dermatology. Feasibility, accuracy, and reproducibility are key elements for a diagnostic method to be useful, hence the importance of the terminology used to describe dermoscopic criteria. Objective: To evaluate the reproducibility of the English descriptive terminology proposed for dermoscopic criteria at the 3rd Consensus Meeting of the International Dermoscopy Society in Brazilian Portuguese. Methods: Nine Brazilian dermatologists independently analyzed the translation of sixty dermoscopic descriptive terms proposed at the 3rd Consensus Conference of the International Society of Dermoscopy. Interobserver agreement index was analyzed using the Fleiss' kappa test. Results: The interobserver agreement of the descriptive terminology in Brazilian Portuguese was considered weak (κ = 0.373; p < 0.05). The interobserver agreement of the descriptive terminology used to describe morphology and arrangement of vascular structures was considered moderate (κ = 0.43; p < 0.05). Study limitations: Our study limitations include the small number of participants and limited regional representation (only 2 out of 5 Brazilian regions were represented). Conclusions: The descriptive English terminology proposed at the 3rd Consensus Conference of the International Dermoscopy Society revealed weak reproducibility and the morphology and arrangement of vascular structures presented moderate reproducibility in Brazilian Portuguese. Despite small regional differences, metaphoric terminology in dermoscopy seems to be the most useful and reproducible system to be adopted in Brazilian Portuguese.